Team, Front cover, Editorial information, Table of Content, Back Cover - Journal Editor (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2012)
J. Trop. Pharm. Chem. 2012. Volume 2 Nomor 1 Team, Front cover, Editorial information, Table of Content, Back Cover